2023
DOI: 10.3390/pr11051505
|View full text |Cite
|
Sign up to set email alerts
|

Research on Low-Carbon Strategies of Supply Chains, Considering Livestreaming Marketing Modes and Power Structures

Abstract: A livestreaming supply chain composed of a single manufacturer and a single streamer in the low-carbon market is examined. Motivated by the actual production and operation, both the manufacturer and the streamer have a chance to dominate the supply chain. Low-carbon strategies and livestreaming marketing modes of the supply chain are studied. The impacts of the consumer’s price sensitivity coefficient, low-carbon preference, and streamer’s promotion sensitivity coefficient on the equilibrium results are furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Cai et al [28] used a differential game model to study the issues of carbon trading limits and trading systems under power structures and consumers' low-carbon preferences, and they analyzed the optimal pricing and carbon emission reduction decisions of supply chain members. Gong et al [29] investigated the selection of low-carbon strategies and live marketing models for supply chains under two power structures. The above literature adequately considers the differences in power structures between enterprises and analyzes the influence of different power structures on enterprise decision-making.…”
Section: Power Structures In Supply Chainsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cai et al [28] used a differential game model to study the issues of carbon trading limits and trading systems under power structures and consumers' low-carbon preferences, and they analyzed the optimal pricing and carbon emission reduction decisions of supply chain members. Gong et al [29] investigated the selection of low-carbon strategies and live marketing models for supply chains under two power structures. The above literature adequately considers the differences in power structures between enterprises and analyzes the influence of different power structures on enterprise decision-making.…”
Section: Power Structures In Supply Chainsmentioning
confidence: 99%
“…Blockchain technology affects the profits and emission reduction decisions of low-carbon supply chain enterprises, while the unequal power structure determines the influence and voice of all parties. Referring to the studies of Xu et al [26] and Gong et al [29], due to different power structures, leaders in the low-carbon supply chain will have different motivations and strategies for emission reduction, which will affect the effect of carbon emission reduction.…”
Section: Problem Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al [1] established game models for a live-streaming supply chain and found optimal strategies for live-streaming members on streaming marketing modes, prices, and carbon emission reduction efforts.…”
Section: Sustainable Supply Chain Design and Managementmentioning
confidence: 99%
“…The adoption of circular economy principles, material recycling, and waste reduction not only serve to enhance the environmental friendliness of manufacturing processes but also result in financial gains and improved profitability [9,26]. Moreover, optimisation of the supply chain is vital to low-carbon SM [27,28]. Efficient logistics and transportation planning have the potential to significantly reduce energy consumption associated with the transportation of products [29,30].…”
mentioning
confidence: 99%